253 PREVALENCE OF FRAILTY IN ADULTS OVER 75 ADMITTED UNDER SURGICAL SPECIALTIES IN A TERTIARY HOSPITAL. (18th November 2021) - Gannon, E; Aherne, E; Khan, I; Nor, N; Murphy, J; O'Mahony, E; Cloney, T; Rafferty, M; Stoneman, S; Murphy, D; Crowley, P; Creed, S; et al.
Abstract: Background: The early identification and comprehensive assessment of frailty in older adult hospital inpatients is associated with improved outcomes. The aim of this study was to identify the prevalence of frailty amongst inpatients admitted under surgical services over the age of 75 in a tertiary hospital. A secondary aim was to identify older adult inpatients under surgical specialities who would benefit from Geriatric Medicine input. Methods: Inpatients over the age of 75 admitted under Surgical specialities were identified by a search of the electronic patient information system iPIMS on 26/08/2021. Patients attending a day service or needing High Dependency or Intensive care Units were excluded. Information was collected using a paper questionnaire from patient records. Frailty was screened by using the Think FRAIL tool. The data was stored on a hospital password protected computer and analysed using Microsoft Excel. Results: 45 were patients admitted under surgical services meeting criteria were identified. The services included Orthopaedics (n = 25), General Surgery (n = 6), Vascular Surgery (n = 2), Cardiothoracic Surgery (n = 8), Neurosurgery (n = 3), and Urology (n = 1). The overall prevalence of frailty indicated by the presence of least one criteria of the Think FRAIL tool reached 75% (n = 34) of patients. A new or worsening functional impairment was present in 66% (n = 30) of patients, altered mental status 29% (n = 13), immobility 71% (n = 32), presence of home supports 60% (n = 27), and residents of long-term care accounted for 9% (n = 4). 51% (n = 23) of patients had a Comprehensive Geriatric Assessment, Orthopaedics (n = 19), Vascular Surgery (n = 1), General Surgery (n = 3). The average time to CGA was 2 days. Conclusion: Co-management models of care like Orthogeriatrics are associated with better outcomes for patients and better outputs for hospitals. There is increasing interest in Ireland and internationally in perioperative multidisciplinary care of older adults undergoing surgery. This study highlights the need to expand co-management and collaborative models of care.